Radiographic Comparative Study Between Bovine Bone Graft and PRF for Socket Preservation for Delayed Implantation (Journal of Hama University, 2020)
The aim of this study was to evaluate bone density and radial bone absorption using cone beam computerized tomography when using ICEBERG.OSS bovine bone grafts and platelet rich fibrin after six months of tooth extraction for delayed implantation.The research sample consisted of 32 cases of single-rooted tooth extraction in 16 patients ranged between 24-46 years with an average age of 37,68 years, and they have symmetric extraction for the study design in a manner (Split mouth design), the cases were divided into two equal groups applied to the first bovine bone graft and the second platelets rich fibrin, and the research was carried out in two stages, tooth extraction and application of grafts with covering of alveolar with collagenous membrane and  cbct was done, and after 6 months the second image was performed and the bone density and alveolar height and width values ​​were measured and the results compared.Both grafts gave good results in preserving the socket, the bovine bone graft was more effective in preserving the socket from absorption, but the platelet rich fibrin was more effective in  the soft tissue healing than bovine graft.The average absorption in the alveolar width in the platelet rich fibrin sample was 1.73 ± 0.594 mm and 1.15 ± 0.475 mm in the bovine taste sample, and the average density of the alveolar socket which put the platelet rich fibrin was 823 ± 110 Hounsfield and the socket with bovine bone was 827 ± 114 Hounsfield.